Investigation on strength characteristics and mechanism of cold mix based on geopolymerization reaction - Fan, Junying; Liang, Hao; Sun, Zhiping; Chen, Zhao (Frontiers in Built Environment, 2023)
Cold mix asphalt is an energy-efficient and eco-friendly pavement material, yet its early strength is deficient. This study investigated the strength augment of cold mix asphalt through modification with geopolymer additives. Macro-strength was assessed via Marshall stability testing under varied geopolymer contents, curing durations, and water immersion conditions. Microscale analysis encompassed fluorescence microscopy to discern geopolymer-asphalt interactions and discrete element modeling to simulate the compression process. Results showed that stability rose and then fell as geopolymer content increased, with an optimal ratio of 4:3 between base asphalt and additive. Stability increased rapidly in the first 3 days of curing and accumulated at a slower rate afterwards. Fluorescence microscopy revealed that geopolymer bonded the asphalt to the aggregate surfaces. Modeling exhibited geopolymer resisted vertical loads and confined the aggregate. In summation, geopolymerization enhances cold mix strength by improving adhesion and generating a rigid 3D network encompassing aggregate particles. The discoveries provide guidance on formulating durable cold mix asphalt utilizing geopolymer additives.